2021
DOI: 10.1002/1878-0261.13028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and tumorigenicity of ascites‐derived tumor cells: mitochondrial oxidative phosphorylation as a novel therapy target in ovarian cancer

Abstract: Ovarian cancer disseminates primarily intraperitoneally. Detached tumor cell aggregates (spheroids) from the primary tumor are regarded as ‘metastatic units’ that exhibit a low sensitivity to classical chemotherapy, probably due to their unique molecular characteristics. We have analyzed the cellular composition of ascites from OvCa patients, using flow cytometry, and studied their behavior in vitro and in vivo . We conclude that ascites‐derived cultured cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Inhibition of mitochondrial OXPHOS is known for preventing the reprogramming of pro-inflammatory M1 macrophages to the anti-inflammatory M2 phenotype, reducing tumor burden. This was further supported by a study where metformin and IACS010759-mediated inhibition of OXPHOS has reduced the tumor burden [ 80 ]. Interestingly, studies have shown that combinatorial treatment with metformin and the glycolytic inhibitor 2-deoxyglucose (2-DG) is effective in a broad spectrum of pre-clinical cancer models [ 81 ].…”
Section: Metabolic Changes In Tamsmentioning
confidence: 73%
“…Inhibition of mitochondrial OXPHOS is known for preventing the reprogramming of pro-inflammatory M1 macrophages to the anti-inflammatory M2 phenotype, reducing tumor burden. This was further supported by a study where metformin and IACS010759-mediated inhibition of OXPHOS has reduced the tumor burden [ 80 ]. Interestingly, studies have shown that combinatorial treatment with metformin and the glycolytic inhibitor 2-deoxyglucose (2-DG) is effective in a broad spectrum of pre-clinical cancer models [ 81 ].…”
Section: Metabolic Changes In Tamsmentioning
confidence: 73%
“…Prior studies have implicated anoikis resistance as a phenotype of metastatic and chemo resistant cells. 43,5,44 45 Given that reversion to the original anoikis state occurred in the absence of stress ( Fig 2D ) we tested if such an acquired ‘tolerance’ rather than permanent resistance (intrinsic), was sufficient to alter in vitro tumorigenic properties. A transwell migration assay revealed that OV90-AnR cells (cells derived from P7) were able to undergo significantly higher migration through fibronectin ( Fig 3A ) as compared to the parental population (P0), and also as compared to cells expanded after exposure to a single round of suspension culture (P1, Fig 3A ) .…”
Section: Resultsmentioning
confidence: 99%
“…Ovarian cancer is the most devastating of gynecological cancers (fifth in cancer deaths among women) and an archetypal example of a cancer that leverages the metastatic hallmark of anoikis resistance for both trancoelomic/intraperitoneal and distant metastasis . [4][5][6][7][8] Accumulation of malignant ascites in the peritoneal cavity occurs as disease progresses, and this process necessitates suspension survival and/or bypass of cell death mechanisms in tumor cells. [9][10][11][12] The precise mechanisms by which cells acquire such anoikis resistance and adapt for apoptosis avoidance as a result of detachment stress remains a subject of intense investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The local low-glucose environment contributes to the expansion of chemical resistance to paclitaxel in ovarian cancer cells, creating a vicious cycle (30). Mitochondrial oxidative phosphorylation (OXPHOS) and the pentose phosphate pathway (PPP) were upregulated in ovarian cancer cells with metastatic capacity (31,32). Glutamate is used by ovarian cancer cells in mitochondrial OXPHOS to produce adenosine triphosphate (ATP) and other biomolecules necessary for aggressive expansion and migration (33).…”
Section: Metabolism Of Ovarian Cancer Cellsmentioning
confidence: 99%